Vibration Assessment of a New Danube Bridge at Komárom - Szabó, Gergely; Völgyi, István; Kenéz, Ágnes (Periodica Polytechnica Civil Engineering, 2022)
In this paper the vortex induced vibration of a cable-stayed bridge with a main span of 252 m was studied at construction stages. Structural FEM and aerodynamic CFD models were made in order to calculate the vibration amplitude of this slender structure. The damping of the pure steel structure and the effect of the tuned mass dampers were measured through on-site vibration tests. Based on the validated structural dynamics model and the simulated aerodynamic parameters, the vortex induced vibration amplitudes were evaluated and compared with the monitoring data gained from accelerometers and wind sensors attached to the stiffening girder during the most critical construction period.